Digital Economic Growth and MSME Development in East Java: A Systematic Literature Review - Anwar, Lukman Hakim (Manajemen Multitalenta Indonesia, 2025)
This study systematically reviews the existing body of knowledge on digital economic growth among Micro, Small, and Medium Enterprises (MSMEs) in East Java, Indonesia. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the review synthesizes empirical evidence from 20 peer-reviewed publications retrieved from Scopus, Web of Science, and Google Scholar published between 2018 and 2024. The analysis focuses on key drivers of digital transformation, including digital literacy, technology adoption, government facilitation, access to digital finance, and platform-based market integration. Findings show that digitalization significantly enhances MSME productivity, market expansion, operational efficiency, and resilience—especially during disruptive periods such as the COVID-19 pandemic. However, growth remains uneven due to gaps in digital skills, limited infrastructure in rural areas, and inconsistent policy implementation. The review also identifies an emerging shift toward the use of e-commerce ecosystems, fintech services, and social-commerce platforms as catalysts for MSME competitiveness in East Java. A conceptual framework is proposed to explain the pathways through which digital capabilities influence economic performance. This review concludes that strengthening digital capacities, inclusive policies, and technological ecosystem support is essential to accelerating MSME-driven digital economic growth in the region.